Analisis Implikasi Permasalahan Wanprestasi dalam Kredit Perbankan (Studi Kasus Putusan MAHKAMAH AGUNG Nomor: 2337 K / PDT / 2009) - Husen, Muhammad Nazim; Rizal, Said (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
In this case the customer (debtor) requires a certain amount of money for the business capital, as a guarantee his debtor submit his certificate letter as collateral to the creditors which in this case is PT. BANK SYARIAH MANDIRI DENPASAR is a Bank financial institution that one of its business activities is to give credit to the community. This journal aims to know that the Bank Mandiri Denpasar has done the agreement to debtors, the method used in this writing normative juridical research is a study conducted or shown in the written rules or other legal materials. The results showed that the creditors admitted that there was an agreement with the debtor that was loaded in Akad al-Murabahah. The contract is stated if the debtor dies then all debtor's debts will be paid by full life insurance, and the debtor dies, but the creditor will only pay the life insurance for 12 (twelve) months, because the debtor has to do the payment rider for 6 (six) months and the next month the borrower dies, the result of remaining installment from the original tenor 84 (eighty four) months which is paid 12 (twelve months) by the debtor must be re- has been reagreed by the beneficiaries of the debtor.